Peningkatan Ketrampilan Pengelolaan Media Sosial Sebagai Sarana Pelestarian Tari Tradisional - Hajidah Fildzahun Nadhilah Kusnadi; Mohammad Insan Romadhan; Tri Pramesti; Aisyah Indha Suwandha; Cherry Ervina Marcely; Olfiana Arista Bora (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The development of digital technology has transformed the way society accesses and appreciates cultural arts, making the preservation of traditional dance require adaptive strategies that use social media. This community service program aims to improve Sanggar Tari Mugi Lestari's social media management skills to support cultural promotion and preservation. The implementation method used a participatory approach comprising several stages: identifying technical needs, training in digital content production, social media management workshops, production simulations, continuous content broadcasting, and performance quality evaluation. The results showed a significant improvement in the partner’s capacity, both in technical production skills (camera operation, lighting, and image capturing) and content management skills (content calendar development, caption and hashtag strategies, and audience engagement). Within two months of implementation, the dance studio successfully broadcast 10 pieces of digital content on Instagram and TikTok, resulting in a notable increase in viewers and interactions, thereby expanding its cultural promotion outreach. Initially lacking equipment, skills, and digital strategies, the studio can now independently manage active social media accounts. In conclusion, strengthening social media management skills has proven effective as a strategy for preserving traditional dance in the digital era, while also creating opportunities for cross-community collaboration, supporting a culture-based creative economy, and contributing to the achievement of Sustainable Development Goals (SDGs 4 and 8). Follow-up efforts will focus on developing more diverse content, exploring digital monetization, and expanding cultural promotion networks.